Invisible Stanley - Brown, Jeff, 1926-2003.; Pamintuan, Macky (New York : Scholastic, 2009)
One morning after a thunderstorm, the Lambchop family is surprised to discover that Stanley is suddenly invisible.
Keywords: Brothers -- Juvenile fiction; Families -- Juvenile fiction; Storms -- Juvenile fiction; Thieves -- Juvenile fiction